Profile of Similarity of Electron Withdrawing Structure Towards Analgesic-Anti-Inflammatory Activity of The Novel Isatin Analogue: Design and Implementation of Phase I Drug Discovery - Hajare, Rahul (International Physiology Journal, 2018)
Isatin (1H-indole-2,3-dione ) and derivatives demonstrate a diverse array of biological activities. Isatin and 5-halo derivatives has reacted to form the schiff’s bases , mannich bases and friedal craft alkylation’s to form C-C, C-N, C=N bonds. From the spectral studies, isatin has undergoes reaction at C-3 and N-1 position and synthesized lead in present schme and seen the similarity of structure and analgesic-anti-inflammatory activity.
Keywords: Schiff’s base; n-benzylation; dimethylformamide; anti-inflammatory; analgesic.